Eco- Industrial parks & Eco-Industrial Cities, The Possibility of Its Future Implication in Iraq (Journal of Engineering, 2013)
Recently new and multiple concepts emerged in the sustainability issues ,which transformed into number of planning and designing policies and strategies that must be committed by the designers and the relevant trends in building ,regarding Iraq and the reality of industrial areas ,especially in Baghdad, which helped to sustain few of it & emerged another with bad reflect ,which for that made it clear the importance of implicating sustainable ecological planning and designing strategies provided by the concept of Eco-industrial parks and the concept of Ecotowns and the future potentials provided ,and the easiness of carrying it out which made it flexible and away to provide a base supported by it for rebuilding and rehabilitation and sustainable regeneration. Accordingly, the research looked for the sustainable planning and designing strategies for industrial areas and the potentials of applying it in Baghdad to propose future planning strategies to rehabilitate and regenerate Iraq industrial areas.